The quilts of Gee's Bend - Beardsley, John.; Museum of Fine Arts, Houston (Atlanta, GA : Tinwood Books in Association with the Museum of Fine Arts, Houston, 2002)
Relates the lives of the women of Gee's Bend, Alabama, who for more than 150 years have made quilts reflecting their history and daily lives. Having worked in isolation for generations and continuing to inhabit the remote plantation land their parents once slaved, they have received unexpected attention from the artistic world.
Introduction : the quilts of Gee's Bend / Alvia Wardlaw -- River Island / John Beardsley -- On the map / William Arnett and Paul Arnett -- Reflections on the art of Gee's Bend / Jane Livingston -- (Quilt portfolios) Work clothes -- My way -- Annie Mae Young -- Housetop -- Family -- Triangles -- Patterns -- Sears corduroy.
"Published in conjunction with the exhibition The Quilts of Gee's Bend organized by the Museum of Fine Arts, Houston"--T.p. verso.
"The quilts reproduced in this book are from the William Arnett Collection of the Tinwood Alliance"--T.p. verso.
Includes bibliographical references (p. 182-183) and index.
Keywords: African American quilts -- Alabama -- Wilcox County -- Exhibitions; African American quiltmakers -- Alabama -- Wilcox County -- Exhibitions; Quilts -- Alabama -- Wilcox County -- History -- Exhibitions; African American women -- Alabama -- Wilcox County -- Exhibitions; Tinwood Alliance -- Exhibitions; Arnett, William -- Art collections -- Exhibitions